2016
DOI: 10.1007/s00246-016-1414-7
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Tp–e Interval and Tp–e/QT Ratio in Children with Mitral Valve Prolapse

Abstract: Although it is considered to be a benign condition, previous studies have shown that a subset of patients with mitral valve prolapse (MVP) may be at risk of ventricular arrhythmia and sudden cardiac death (SCD). Previous studies have suggested that the interval between the peak and the end of the T wave (Tp-e) can be used as a marker for the transmural dispersion of repolarization. Increased Tp-e interval and Tp-e/QT ratio are associated with ventricular arrhythmias and SCD. The aim of this study was to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…28 Demirol et al also observed significantly higher values for the Tp-e interval, Tp-e/QT, and Tp-e/QTc ratios in MVP patients as compared to controls in a study involving 110 MVP patients and 107 controls in children. 21 Our study discovered that the Tp-e interval and Tp-e/QTc ratio were significantly higher in MVP patients in comparison to the control group. This differs from other studies because patients with ST-T segment changes on the ECG were excluded.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…28 Demirol et al also observed significantly higher values for the Tp-e interval, Tp-e/QT, and Tp-e/QTc ratios in MVP patients as compared to controls in a study involving 110 MVP patients and 107 controls in children. 21 Our study discovered that the Tp-e interval and Tp-e/QTc ratio were significantly higher in MVP patients in comparison to the control group. This differs from other studies because patients with ST-T segment changes on the ECG were excluded.…”
Section: Discussionmentioning
confidence: 48%
“…19,20 Similarly, pediatric patients with MVP have been found to have significantly higher QTc dispersion compared to healthy controls. 7,21 In our study, we excluded individuals with pathological findings such as frequent VEA, bundle branch block, and ST-T changes from the analysis and only evaluated subclinical cases. Despite this, we discovered that the MVP group's QTc dispersion was considerably higher than that of the healthy peers (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Demiro M et al 15 observed that QT dispersion and QTC dispersion were significantly higher in patients with MVP. Still, they reported no significant differences between the groups in terms of QT and QTc.…”
Section: Discussionmentioning
confidence: 95%
“…QTc intervali normal olan hastalarda bile ventriküler aritmileri ve ani ölümü öngören Tp-e intervalinin obezlerde ventriküler aritmiler için invaziv olmayan EKG tarama yöntemi olarak kullanılabileceğini belirten çalışmalar mevcuttur (26). Tp-e/QT oranının da ventriküler aritmi ve ani ölüm riski açısından kullanılan bir diğer duyarlı parametre olabileceği bildirilmiştir (26,27). Çocukluk çağında, Tp-e intervalini ani ölüm riskiyle ilişkili olarak değerlendiren, kardiyak mortalite üzerine etkilerini net olarak açıklayan bir çalışmaya tarafımızca rastlanmamıştır.…”
Section: Discussionunclassified